Photonics of halogenated zinc(II) and cadmium(II) dipyrromethene complexes - Aksenova, Yulia V. (Colorants)
This article compares spectroscopic properties of the series of dipyrromethene dyes, namely their complexes of boron (III), zinc(II) and cadmium(II) with the halogenated ligands of the same structure. Absorption and emission spectra, lifetimes of long-lived emission and quantum yields of luminescence were studied as the functions of molecular structure of dipyrromethene complexes. The role of the position and nature of a substituent in a ligand, polarity of a solvent and temperature of media were also investigated. The studies demonstrate that replacing the central atom boron(III) by zinc(II) decreases the fluorescence quantum yield, indicating the increased role of non-radiative processes in excitation energy deactivations such as intersystem crossings. In addition, according to the heavy atom effect, the efficiency of intersystem crossings in halogen-substituted zinc(II) and cadmium(II) dipyrromethene complexes is higher than in the corresponding boron fluoride dipyrromethenes (BODIPY), which leads to increase in phosphorescence at low temperatures (frozen solutions). The obtained results make it possible to carry out further investigations of potential sensory properties that are required for systematic use of halogenated dipyrromethene complexes for the creation of modern optical oxygen sensors and singlet oxygen photosensitizers for photodynamic therapy or photocatalytic oxidative reactions.